NATO and Caspian security : a mission too far? - Sokolsky, Richard; Charlick-Paley, Tanya, 1968-; Rand eBooks (Santa Monica, CA : RAND, 1999)
This report attempts to put the Caspian Basin and Central Asia into a comprehensive strategic perspective at a time when NATO is increasingly concerned with challenges on its periphery. The authors examine NATO's interests, capabilities, and constraints as well as the salient trends and factors shaping the regional security environment. In spite of the region's potential energy riches and the jockeying for influence among major powers and oil interests, the authors suggest that NATO should see the region as a potential quagmire rather than as a vacuum waiting to be filled. The report discusses Western objectives and interests in the Caspian, internal and intraregional threats to Western interests, the competition for influence among outside powers, transnational threats, Caspian oil and energy security, and implications for NATO and Western policy and planning. The authors conclude that the West has limited interests and leverage in the Caspian Basin, and the Alliance should focus on promoting the restructuring and professionalization of indigenous armed forces, while resisting new commitments and security responsibilities in the region.
"Project Air Force."
Includes bibliographical references (p. 99-113).
Also available on the internet via WWW in PDF format.
Keywords: North Atlantic Treaty Organization; National security -- Asia, Central; National security -- Caspian Sea Region; National security -- Caucasus; Asia, Central -- Foreign relations; Asia, Central -- Strategic aspects; Caspian Sea Region -- Defenses; Caucasus -- Foreign relations; Caucasus -- Strategic aspects; Electronic books